Emerging trends and research foci of epithelial–mesenchymal transition in gliomas: A scientometric analysis and review - Xing, Yang; He, Minghua; Su, Zhenjin; Yasinjan, Feroza; Liu, Jiankai; Wang, Hong; Cui, Jiayue; Hong, Xinyu (Frontiers in Oncology, 2022)
Background Epithelial–mesenchymal transition (EMT) is a key factor in the invasion and migration of glioma cells, and the study of EMT in gliomas has become a hot topic over the past decade. Scientometric analysis is gaining more attention since it can obtain hot topics and emerging trends in a research field. This article analyzed the research related to EMT in gliomas for the first time, including descriptions of research situations, evaluations of research foci, and predictions of emerging trends. Methods We searched the topic-related original articles from January 2012 to December 2021 in the Web of Science Core Collection (WoSCC) by using a specific strategy, and a total of 1,217 publications were obtained. The WoS platform, VOS viewer, and CiteSpace were used to analyze the annual distribution of publications and citations, authors and density of keywords, and other analyses including countries, institutions, references, clustering, burst analysis, and the timeline view of keywords. Results Scientometric analysis identified that the study of EMT in gliomas has developed fast and received continuous attention in the last decade. Based on the results of data analysis, most publications on the topic came from China, and the United States had the highest betweenness centrality. The top 10 co-cited references revealed the landmark documents that had greatly promoted the development of this field. The major focus is on the cellular and molecular mechanisms of EMT in gliomas, and the therapy related to EMT target and non-coding RNAs has been developing fast in recent years. Conclusions This study revealed the intimate connections between EMT and gliomas, and the complex mechanisms regulating EMT in gliomas had been studied widely in the last decade. Exploring the deep mechanisms of EMT in gliomas is the foundation of the targeted inhibitions, which can promote the development of therapies for gliomas.